2010
DOI: 10.1086/653534
|View full text |Cite
|
Sign up to set email alerts
|

Palivizumab‐Resistant Human Respiratory Syncytial Virus Infection in Infancy

Abstract: Palivizumab-resistant respiratory syncytial virus was isolated from an infant treated with palivizumab. A stable mutation at codon 276 led to a nearly complete resistance to palivizumab. Additional studies revealed a second mutation at codon 272. Further passage of the virus led to a complete loss of binding of palivizumab.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 15 publications
0
45
0
2
Order By: Relevance
“…The determination of epitopes targeted by antibodies is useful for understanding virus escape (1), antibody optimization (2,3) and epitope-based design of vaccines (4). Structure determination (by, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The determination of epitopes targeted by antibodies is useful for understanding virus escape (1), antibody optimization (2,3) and epitope-based design of vaccines (4). Structure determination (by, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The scarce information on patients that is available comes from studies on individuals who received PZ, and it has been reported recently that a PZ-resistant HRSV isolated from patients who had received PZ had amino acid substitutions at positions 272, 275 and 276 [47][48][49]. Also, a study of natural polymorphisms in the F protein of HRSV showed that mutations Asn262Asp and Ser275Phe isolated from immunoprophylaxis-naïve subjects are associated with resistance to palivizumab [48].…”
Section: Discussionmentioning
confidence: 99%
“…1 40) and was dominant in Canada between 2008 and 2010 41) . Adams et al showed that the N276S mutation in RSV -A leads to a decrease in NT activity against palivizumab 47) . This mutant virus was isolated from preterm infants 4 months old who were administered palivizumab but were treated in an intensive care unit for RSV infection.…”
Section: Palivizumab Resistancementioning
confidence: 99%
“…On the other hand, they also reported that the detection frequency of palivizumab -resistant mutations in RSV isolated from patients receiving palivizumab treatment was 5.4% 43) . The amino acid at position 276 of the F protein is generally asparagine (N) for RSV -A and serine (S) for RSV -B 40,47) . It is possible that the N276S mutation in RSV -A and S276N mutation in RSV -B appeared due to hybridization between the subgroups, natural mutation and so on.…”
Section: Palivizumab Resistancementioning
confidence: 99%